The Use of Role Playing Learning Methods and Mystery Box Media to Improve Students' Learning Outcomes in Class VI SDN Lebakrejo 4 Purwodadi - Kumala Dewi Pertiwi; Bunga Ayu Dibtasari; Achmad Chusairi (Justek : Jurnal Sains dan Teknologi, 2022)
Abstract: This research is a classroom action research (CAR) that aims to find out whether applying the role playing method and mystery box media can improve the learning outcomes of class VI students at SDN Lebakrejo 4 Purwodadi on the science content of the solar system material. The method used in this study is observation, documentation, and learning outcomes assessment tests. The results showed that by using the role playing method and mystery box media there was an increase in student learning outcomes from pre-action to cycle II by 55.56%. The class average also increased by 29.89 from pre-action to cycle II.Abstrak: Penelitian ini merupakan penelitian tindakan kelas (PTK) yang bertujuan untuk mengetahui apakah dengan menerapkan metode role playing dan media mystery box dapat meningkatkan hasil belajar siswa kelas VI di SDN Lebakrejo 4 Purwodadi pada muatan IPA materi tata surya. Metode yang digunakan dalam penelitian ini adalah observasi, dokumentasi, dan tes penilaian hasil belajar. Hasil penelitian menunjukkan bahwa dengan menggunakan metode role playing dan media mystery box terjadi peningkatan hasil belajar siswa dari pra tindakan ke siklus II sebesar 55,56%. Rata-rata kelas juga meningkat sebesar 29,89 dari pra tindakan ke siklus II.